Projeto: readequação do mix de produtos - Schneider, Rodrigo (Universidade do Vale do Rio dos Sinos, 2017)
This paper presents a proposal for improvement of the internal process in the control format of portfolio of product mix of company X. In this work was developed the complete project plan, including costs, schedule and all topics to be discussed that the Project Management Institute (PMI) through Project Management Body of Knowledge (PMBOK) is recommended in a project plan was developed. The project itself is a process improvement, seeking a control in the portfolio of active products as well as the process of developing suppliers. The management of this project is important for the management of the portfolio of active products in the company.
Keywords: Mix de produtos; PMBOK; Desenvolvimento de fornecedores; Product mix; PMBOK; Supplier development